Design of English Translation System Based on Deep Learning - Ting, Yang (Journal of physics. Conference series, 2021)
Intelligent translation software is one of the important tools for people to learn, but the existing intelligent translation system usually needs to be further improved in terms of the flexible application of phrases and the accurate expression of professional vocabulary. The translation system based on deep learning designed in this paper mainly includes professional vocabulary database module, memory analysis module, English translation module and correction module. The professional vocabulary module accurately classifies words related to various disciplines. The memory analysis module compares the professional vocabulary usage in published documents on the Internet to analyze and memorize, so as to recommend relatively accurate professional vocabulary to enter the translation module. Need to enter the correction module to complete the correction of grammar and phrases, and finally complete the translation task with higher accuracy.